Advances in ovarian cancer treatment using a combination of statins with other drugs - Xia, Lei; Ding, Shichao; Wang, Xuezhen; Zhang, Xiaoyu; Zhu, Lin; Zhang, Hairong; Li, Huirong (Frontiers in Pharmacology, 2023)
The treatment of recurrent and chemo-resistant ovarian cancer is an issue that must be addressed. The role of statins in the treatment of ovarian cancer is gaining popularity. However, the therapeutic effect of statins varies significantly among different types of tumors due to the high heterogeneity of ovarian cancer. Understanding the mechanism of statins for treating ovarian cancer and improving clinical treatment effects by drug combination would be a promising alternative.